Role of Neutrophil-Derived S100B in Acute Myocardial Infarction Patients From the Han Chinese Population - Cheng, Minghui; Su, Xu; Liu, Dan; Tian, Xiaoxiang; Yan, Chenghui; Zhang, Xiaolin; Han, Yaling (Frontiers in Cardiovascular Medicine, 2021)
Objective: This study aimed to clarify the novel role of homeostatic calmodulin S100B and determined whether S100B genetic variants affected atherosclerosis progression in acute myocardial infarction (AMI) patients. Methods: Plasma levels of S100B were measured systemically in AMI patients, stable angina pectoris patients, and control subjects. S100B was obtained from the human coronary artery thrombi using a thrombectomy catheter and quantified via immunohistochemical analysis, qRT-PCR and Western blot analyse. We also screened for S100B variations (rs9722, rs9984765, rs2839356, rs1051169, and rs2186358) via direct sequencing, and investigated the relationship between these variants and AMI patients in the Chinese Han population. Results: Plasma S100B levels increased significantly in AMI patients compared to the levels in stable angina pectoris patients and control subjects (119.45 ± 62.46, 161.96 ± 73.30, and 312.91 ± 127.59 pg/ml, respectively). Immunohistochemical staining results showed that S100B expression was increased in the neutrophils of coronary artery thrombi obtained from AMI patients, as compared to that in normal blood clot, and S100B expression was significantly increased in fresh thrombi tissues, as compared to that in organized thrombi tissues. Western blot and qRT-PCR analysis showed that S100B expression increased in coronary artery thrombi, as compared to that in normal blood clots. After pre-treating the neutrophils with siRAGE, the neutrophils migration induced by S100B were abolished through the NFκB-IL1β/IL6 signaling pathway. Compared to their corresponding wild-type genotypes, the S100B rs9722 variant was associated with increased susceptibility to AMI (OR = 1.35, 95%CI: 1.12–1.65, P = 0.02). Individuals with the S100B 9722 A allele had higher plasma S100B levels than those with the G allele in control subjects and AMI patients (141.70 ± 76.69 vs. 107.31 ± 56.05 and 347.13 ± 148.94 vs. 273.05 ± 133.62, respectively). Conclusions: Levels of neutrophil-derived S100B, a novel homeostatic calmodulin, were elevated in the early stages of myocardial infarction. The S100B rs9722 allele was independently associated with AMI patients in the Han Chinese population.